TRANSFORMER RELIABILITY ANALYSIS USING THE WEIBULL DISTRIBUTION METHOD (CASE STUDY OF THE POWER TRANSFORMER AT THE KOTA BARU PONTIANAK SUBSTATION) - Chaniago, Muhammad Ilham; Purwoharjono, Purwoharjono; Gianto, Rudy (Faculty of Engineering, Universitas Tanjungpura, 2024)
Reliability is the probability that a component or system will be able to operate according to the desired function for a certain period of time when used under specified operating conditions. To determine reliability in operational terms, a more specific definition is needed, namely a description of the failure that is not confusing and can be observed, identification of the time unit, and the system being observed must be in normal environmental and operating conditions. Transformer reliability is greatly influenced by two things, namely disruption and maintenance of the transformer. Scheduled and regular maintenance can increase transformer reliability, however incomplete and poorly scheduled maintenance will result in the transformer not operating or serving more often. The Weibull distribution is a distribution that has an important role, especially in matters of reliability and maintainability analysis. The Weibull distribution is often used as an approach to determine the characteristics of the damage function because changes in value will result in the Weibull distribution having certain properties or being equivalent to a certain distribution. This distribution is a versatile distribution that can take on the characteristics of other types of distribution, based on the values of the form parameters. The Weibull distribution has several reliability indices such as failure rate and MTTF (Mean Time To Failure). Based on the calculation results, power transformer 1 has an average failure rate of 0.0015 times/day, and an MTTF of 714.0685 days or 1.9564 years. Meanwhile, power transformer 3 has a failure rate of 0.0009 times/day, and an MTTF of 1587.6033 days or 4.3496 years. It can be said that power transformer 3 has much better failure rate and MTTF values than power transformer 1. The results shows that power transformer 3 shows better overall performance with a lower failure rate and higher MTTF.